The future of the international exchange rate system - Wolf Schäfer (Europa-Kolleg Hamburg, Institute for European Integration, 2010)
The revival of a multilateral exchange rate system (ERS) with one single anchor currency and binding global rules for national exchange rate management is not a viable or realistic option. It is more realistic that the present 3-polar ERS in the medium term could dynamically enlarge to a 4-polar - in the long run even to a multipolar - system especially when taking China into account. In this view, the global ERS is likely to be extensively characterized by a small number of competing anchor currencies (currency oligopoly) which float vis-à-vis each other and to which pegs and managed floats are attached (satellite currencies). Globalisation contradicts international monopolies including monopoly currencies. Globalisation stimulates international competition including anchor currency competition. This paper underlines that this is why there is no way back to Bretton Woods or to any similar system based on only one single world anchor currency.
Keywords: E44; E58; F31; F33; F55; G15; 320; exchange rate systems; Bretton Woods; anchor currency; currency competition; globalisation